Bionic Ring Grooves Design and Experiment of the Suction Cup Applied in Oil-Immersed Substrate - Jin Xu; Lin Wang; Dexue Zhang; Xiaojie Shi; Tingkun Chen; Qian Cong; Chaozong Liu (Lubricants, 2023)
The vacuum suction cup is often used as an end effector and widely used in wall-climbing operations. However, there are few vacuum suction cup designs and applications for oil-immersed substrates. Inspired by the surface morphology of the octopus sucker, bionic suction cups with different numbers, diameters, and spacings of the ring grooves were designed. Their normal adsorption force was evaluated on the untreated and polished steel plate in oil. The test results showed that ring grooves positively affected the adsorption force. The bionic suction cup with a groove number of 3, a diameter of 0.5 mm, and a spacing of 3 mm was the most excellent in the test. It achieved normal adsorption forces of 54.83 ± 0.48 N and 43.89 ± 0.69 N on the untreated and polished steel plate. Compared with the standard suction cup, it increased by 32.31% and 12.28% on the untreated and polished steel plate. The regression model between the normal adsorption force and design factors was established based on the adsorption force test results, and the influence law of the ring groove structure parameters on the adsorption force of suction cups on oil-immersed substrates was analyzed. The order of significant effects of groove design parameters on normal adsorption forces was groove diameters, spacings, and numbers. The finite element analysis (FEA) results show that the ring grooves could significantly increase the contact pressure, frictional stress, and sliding distance between the suction cup and the substrate. The ring groove structure effectively improves the adsorption force of the suction cup on the oil-immersed surface by forming a more effective seal and increasing the friction force and adsorption area. This study could provide a reference for developing the actuator of the oil-immersed or lubricated climbing machine.